Determination of Pesticides by Solid Phase Extraction Based on Central Composite Design - NIAKI†, T.T.; KHOSRAVI*, K.; GHEZEL AYAGH†, P. (Asian Journal of Chemistry, 2009)
Pesticides used frequently in farmlands and homes around the world, which easily passes to agricultural products. Therefore, optimum analyses of these widely used compounds are urgently needed. In this study, our main aim is to determine the effects of sorbent, solvent desorption, flow rate, sample volume and methanol desorption on the extraction efficiency for parathion- methyl, azinfos-ethyl and isoproton according to the central composite design. Each factor and their combinations were studied and the optimum conditions for an solid phase extraction were determined in which 32 mL solvent with a 2.28 mL min-1 flow rate can extract 59.45 mL sample in a short time. This method was used due to its limited data requirement and the frequency of its use in recent studies.